Assessing Assessment: Examination of pre-service physics teachers' attitudes towards assessment and factors affecting their attitudes - BEKİROĞLU, FERAL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2009)
The purpose of this study was to determine pre-service physics teachers' attitudes towards assessment. It was also aimed to examine the factors affecting their attitudes. Two factors were considered. The first was difficulties that pre-service teachers experienced relating to assessment. The second factor was teachers' self-efficacy regarding their ability to assess. The difficulties were divided into external and internal. Internal difficulties depended on pre-service teachers' assessment skills and their subject matter knowledge, and represented the difficulties that they encountered during preparation and evaluation of assessment methods. External difficulties, on the other hand, depended on the external factors such as school policy and facilities that might affect pre-service teachers' classroom assessment implementation. A parallel mixed-methodology approach was utilized during the data collection and analysis. This paradigm combined both qualitative and quantitative methods to give both breadth and scope to the research. The pre-service physics teachers' general attitude towards assessment was determined as close to constructivist. Knowledge about the subject assessed and university entrance examination were found to be the common factors that affected pre-service teachers' predispositions for action. Conclusions carry implications for science teacher education in Turkey and other countries where educational reforms have been implemented.
Keywords: PROFESSIONAL-DEVELOPMENT; CLASSROOM ASSESSMENT; SCIENCE-EDUCATION; KNOWLEDGE; REFORM